The impact of seed priming and aging on physiological performance of chickpea under different irrigation treatments - Hosseinzadeh-Mahootchi, Ayda; Ghassemi-Golezani, Kazem (Plant Breeding and Seed Science, 2012)
A sub-sample of chickpea (Cicer arietinum L. cv.ILC482) seeds was kept as control and two other sub- samples were aged at 40 °C for 3 and 5 days. Consequently, three seed lots with different levels of vigor were provided. These seed lots were soaked in distilled water at 15°C for 12 and 18 hours and then dried back to initial moisture content at a room temperature of 20-22°C. Then seeds were sown in the field as split plot factorial based on RCB design. Hydro-priming improved leaf chlorophyll content index of plants from different seed lots. Hydro-priming also enhanced stomatal conductance of plants from all seed lots under all irrigation levels, but this advantage for plants from low vigor seed lots particularly under limited irrigations was higher than that for other treatments. Plants from high vigor seed lot under different irrigation treatments had higher relative water content, compared with those from low vigor seed lots. Hydro-priming improved relative water content, membrane stability and grain yield of chickpea plants from different seed lots under various irrigation treatments. It was concluded that hydro-priming to some extent can repair aged seeds and improve their performance under different irrigation treatments.